2005
DOI: 10.1200/jco.2005.20.537
|View full text |Cite
|
Sign up to set email alerts
|

Sentinel Lymphadenectomy Does Not Increase the Incidence of In-Transit Metastases in Primary Melanoma

Abstract: There is no relationship between SLND and ITM. Recent reports to the contrary reflect analysis of significantly smaller cohorts not matched for confounding variables such as T stage. The phase III Multicenter Selective Lymphadenectomy Trial will definitively settle the issue; until then, use of SLND, the most accurate staging procedure for early-stage melanoma, should continue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 66 publications
(41 citation statements)
references
References 18 publications
2
39
0
Order By: Relevance
“…Overall regional nodal and systemic recurrence of 5.0% in our study group during the 46 months follow-up period is quite similar to other recent published data (22,(24)(25)(26)(27)(28)(29). The false negative rate of 1.3% is less than 5% that is generally considered acceptable (28).…”
Section: Discussionsupporting
confidence: 90%
“…Overall regional nodal and systemic recurrence of 5.0% in our study group during the 46 months follow-up period is quite similar to other recent published data (22,(24)(25)(26)(27)(28)(29). The false negative rate of 1.3% is less than 5% that is generally considered acceptable (28).…”
Section: Discussionsupporting
confidence: 90%
“…Lymphatic mapping and selective SLN excision in patients with melanoma is a minimally invasive procedure, which allows for the identification of patients at-risk for lymph node metastasis who should undergo a full therapeutic tumordraining lymph node dissection. Recent studies have confirmed the SLN procedure to be safe and offers a possible survival benefit (23,24,43). Routine application of this procedure in patients with early stage melanoma presents a unique translational setting to study adjuvant therapies in vivo aimed at the potentiation of immune reactivity within the SLN.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that SNB could increase the risk of in-transit metastasis and recurrence rates [31,32]; however the current available evidence, including a randomized controlled trail, has demonstrated that this is not a genuine concern [33][34][35][36], with an explanation leading towards a more aggressive tumor biology in these patients than attributable to the SNB.…”
Section: Accurate Staging and Defining Prognosismentioning
confidence: 86%